2016
DOI: 10.3233/jad-160893
|View full text |Cite
|
Sign up to set email alerts
|

Is Salivary Chromogranin A a Valid Psychological Stress Biomarker During Sensory Stimulation in People with Advanced Dementia?

Abstract: Salivary chromogranin A (sCgA) is gaining attention as a biomarker of psychological stress. The objective of this work was to determine whether individualized music intervention and multisensory stimulation environment (MSSE) in a Snoezelen room produce changes in sCgA in severely demented older patients, and to assess the possible existence of differences in sCgA levels between the two types of interventions. Older adults with severe dementia (n = 22) were randomly assigned to two intervention groups. They pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
29
0
4

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(33 citation statements)
references
References 56 publications
0
29
0
4
Order By: Relevance
“…Further data extraction of 141 full‐text articles excluded 135 papers based on the inclusion criteria. Although six papers met the inclusion criteria, three papers were from the same research project as confirmed by the study author . Thus, a total of four studies were included in this review as shown in Figure .…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Further data extraction of 141 full‐text articles excluded 135 papers based on the inclusion criteria. Although six papers met the inclusion criteria, three papers were from the same research project as confirmed by the study author . Thus, a total of four studies were included in this review as shown in Figure .…”
Section: Resultsmentioning
confidence: 99%
“…Music was played through a compact disc (CD) player or a computer in the participant's room, in a private/quiet room or a familiar area. Trained professionals and a research assistant delivered the intervention. In one study, it was stated only that the participants passively listened to their preferred music, while in another study, the music therapist prepared the music playlist but the participants listened to the music without interaction with the therapist .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations